Analysis of Mathematics Learning Difficulties in Material Greatest Common Factor Class VII - Muthmainnah, M (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
In Class VII, some students still need help finding the most significant common factor of several numbers. This research aims to describe the difficulties experienced by students in finding the Greatest Common Factor (FPB) of several numbers. The subject of this research was 1 class VII student of SMPII Lukman Al-Hakim 02 Batam. The object of this research is the difficulty of learning mathematics in the Greatest Common Factor (FPB) material. The data collection technique in this research was conducting interviews, giving test questions, and documenting 1 class VII female student. Based on the interview results, it was clear that the student needed help working on the questions and understanding the FPB material. Apart from that, the test result showed that students were both in ordinary questions and stories; students are less able to do them, so they need repetition and learning to be done so that their understanding of the mathematics of the FPB material can be understood well. The difficulties were: (1) Students needed to correct their carrying out division calculation operations in FPB questions; (2) Students needed help concluding the final answers to FPB questions. This research implies that mathematics teachers must emphasize instilling the concept of FPB material, ensuring that students have mastered division arithmetic operations in solving FPB problems.